Analisis Kebijakan, Strategi dan Analisis SWOT Pengelolaan Usaha Rumput Laut Nelayan Daerah Pesisir Pantai Amal Kota Tarakan - Ardiyansyah, Riyans; Hasanah, Nurjannatul (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
This study aims to analyze the policy strategy for the development of effective effort to increase the income of seaweed fishermen. The data were collected through observation, interview, questionnaire and documentation. Data were analyzed by using descriptive analysis, indicator analysis and policy succesfull, and SWOT analysis. Results showed that seaweed fishermen have problems associated with human resources, capital, facility availability, marketing of seaweed product, seaweed seeds supply, weather and networking. The policies and efforts which have been done by local government in Tarakan have not solved the problems yet. This study suggest to maximize the strength and opportunity (SO strategy), utilize the internal strength and minimize external threaten (ST strategy), utilize the opportunity and minimize the weakness (WO strategy) and minimize weakness and anticipate threaten (WT strategy).